Patient Satisfaction with Healthcare Services Among Inpatients in The Covid-19 Isolation Room - Budhi Setianto; Akas Yekti Pulihasih; Agus Aan Adriansyah; Nikmatus Sa’adah (Jurnal Ilmiah Kesehatan, 2022)
Patient care in the isolation room differs from other rooms, including strict hygiene, proper personal protective equipment, and minimal patient contact. Furthermore, this study aims to portray patient satisfaction with healthcare services among inpatients in the COVID-19 isolation room. It was a descriptive study using a retrospective descriptive methodology. The population was inpatients in the COVID-19 isolation room at Surabaya Islamic hospital for January-May 2021. In addition, the sample was 128 respondents with a total sampling method. The authors used a questionnaire portraying patient satisfaction with health care services based on reliability, assurance, tangible, empathy, and responsiveness dimensions. The data was processed descriptively in a frequency distribution table. The results showed that respondents were satisfied with the reliability dimension (the ability of doctors and nurses to explain, listen, and speed up handling complaints). In addition, they were satisfied with tangible (room facilities, cleanliness of rooms, cleanliness of beds and bathrooms); empathy (attention of doctors, the ability of nurses to motivate and communicate well); assurance (friendly and polite healthcare services, safe healthcare services, and good healthcare service), and responsiveness (fast and accurate healthcare treatments, diagnostics, and easy healthcare procedures). Thus, inpatients in the COVID-19 Isolation Room at Surabaya Islamic hospital for January-May 2021 were satisfied with healthcare services based on reliability, assurance, tangible, empathy, and responsiveness dimensions. However, the empathy dimension had the lowest score among the five dimensions. So, emotional intelligence training is essential to improve health workers' empathy for patients.